A sustainable and rigid-flexible coupling cellulose-supported poly(propylene carbonate) polymer electrolyte towards 5 V high voltage lithium batteries. (10th January 2016) - Zhao, Jianghui; Zhang, Jianjun; Hu, Pu; Ma, Jun; Wang, Xiaogang; Yue, Liping; Xu, Gaojie; Qin, Bingsheng; Liu, Zhihong; Zhou, Xinhong; Cui, Guanglei
Graphical abstract: Polymer power: application of the polymer electrolyte based on rigid-flexible coupling cellulose-supported poly(propylene carbonate) polymer electrolyte which exhibits high voltage window and high ionic conductivity to match with LiNi0.5 Mn1.5 O4 cathode leads to cells that exhibits better cyclic stability and rate performance compared to commercial separator with liquid electrolyte. Highlights: A novel type GPE (gel polymer electrolyte) material based on poly(propylene carbonate) was developed. The cyclability and rate performances of LiNi0.5 Mn1.5 O4 /lithium cell were improved at 5 V cut-off potential. The GPE can prevent the Mn 2+ deposition on the anode surface. The LiNi0.5 Mn1.5 O4 /Li cell based target-GPE can operate at the elevated temperature. Abstract: Inspired by their higher energy density, high voltage lithium ion batteries (LIBs) have been given great attention recently. However, decomposition of traditional liquid electrolyte hinders the development of high voltage LIBs. Herein, we explored a sustainable and rigid-flexible coupling cellulose-supported poly(propylene carbonate) (PPC) polymer electrolyte for LiNi0.5 Mn1.5 O4 -based batteries. The incorporating of robust cellulose as skeleton effectively surmounts the drawback of poor mechanical integrity of the gel polymer electrolyte. It was demonstrated that the polymer electrolyte exhibited wider electrochemical window (up to 5.0 V), higher ion transference number (0.68) and higher ionic conductivity (1.14 mS cm −1 ) compared to liquid electrolyte with commercial separator at 25 °C. Thus, 5 V high voltage batteries with this kind polymer electrolyte display excellent capacity retention and superior rate performance for at room temperature. The Above mentioned attracting characteristics would endow PPC-based polymer electrolyte a promising candidate for high energy density LIBs.